Randomized crossover study investigating daily versus on-demand vulvar Visnadine spray in women affected by female sexual arousal disorder. (1st February 2018) - Caruso, Salvatore; Mauro, Diletta; Cariola, Maria; Fava, Valentina; Rapisarda, Agnese Maria Chiara; Cianci, Antonio
Abstract: The aim of the study was to verify the efficacy of vulvar Visnadine spray in premenopausal women affected by female sexual arousal disorder (FSAD). Thirty-eight women aged 25–40 years affected by FSAD were enrolled in the randomized crossover study, by two possible sequences: on-demand, washout, daily (A sequence); and daily, washout, on-demand (B sequence). The Female Sexual Function Index (FSFI) and the Female Sexual Distress Scale (FSDS) were used to assess sexual function and sexual distress, respectively. Color Doppler ultrasonography was used to measure clitoral blood flow. The study had two follow-ups at 30 (T1) and 60 days (T2). Thirty-one women completed the study. Mean (SD) sexual activity and vulvar Visnadine spray usage was 1 ± 0.9 weekly during on-demand administration for both the sequences (Vs T0, p  = NS). The mean sexual activity during daily usage was 2 ± 0.9 (Vs T0, p  < .004) and 2 ± 0.8 (Vs T0, p  < .001) for A and B sequences, respectively. FSFI total score, particularly genital arousal, improved more during the daily than during on-demand phases of both sequences ( p  < .001). Finally, clitoral blood flow improved significantly during daily usage of both the sequences ( p  < .001). Our study suggests that vulvar Visnadine spray could improve sexual performance of women affected by FSAD, producing changes in subjective and objective sexual aspects.